Estimating safety effects of adaptive signal control technology using the Empirical Bayes method. (February 2018) - Khattak, Zulqarnain H.; Magalotti, Mark J.; Fontaine, Michael D.
Abstract: Introduction: Adaptive signal control technology (ASCT) has long been investigated for its operational benefits, but the safety impacts of this technology are still unclear. The main purpose of this study was to determine the safety effect of ASCT at urban/suburban intersections by assessing two different systems. Method: Crash data for 41 intersections from the Pennsylvania Department of Transportation (PennDOT), along with crash frequencies computed through Safety Performance Functions (SPFs), were used to perform the Empirical Bayes (E-B) method to develop crash modification factors (CMF) for ASCT. Moreover, a crash type analysis was conducted to examine the safety impact of ASCT on a regional scale and the variation of safety among type of crashes observed. Results: The results from this study indicated the potential of ASCT to reduce crashes since the Crash Modification Factor (CMF) values for both ASCT systems (SURTRAC and InSync) showed significant reductions in crashes. Average CMF values of 0.87 and 0.64 were observed for total and fatal and injury crash categories at a 95% confidence level, and results were consistent between systems. While a reduction in the proportion of rear end crashes was observed, the change was not determined to be statistically significant. The overall distribution of crash types did not change significantly when ASCT was deployed. Conclusion and practical application: The results indicate that safety benefits of ASCT were generally consistent across systems, which should aid agencies in making future deployment decisions on ASCT. Highlights: We evaluated the safety effects of adaptive signal control technology (ASCT) at urban/suburban intersections. Multiple ASCT systems (SURTRAC and InSync) were assessed using Empirical Bayes before after and crash type analysis. ASCT deployment was found to be associated with average CMF values of 0.87 and 0.64 for total and fatal and injury crashes. The safety benefits of ASCT were generally consistent across both systems.